LIVER CANCER ASSOCIATED WITH HEPATITIS B VIRUS INFECTION IN A CHILD: A CASE REPORT - Karina Pharamita Dewi; Rendi Aji Prihaningtyas; Bagus Setyoboedi; Sjamsul Arief (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Two-thirds of primary liver tumors in children are malignant. Hepatoblastoma (HBL) accounts for 40-60 percent of pediatric liver tumors and is the most common malignant liver tumor. Hepatocellular Carcinoma (HCC) is the second most common malignancy in children, accounting for approximately 20% of cases. Both malignant liver tumors have similar clinical and imaging features, but different prognosis and treatment. Purpose: This report aims a case of liver cancer related to hepatitis B virus infection in a child. Case analysis: A 15-year-old girl presented with a two-month history of right upper quadrant pain along with abdominal distension, weight loss, back pain, anorexia, nausea, weakness and fatigue for 5 months prior to admission. Physical examination revealed a hard, firm mass with a bumpy surface in the right upper quadrant of the abdomen and splenomegaly. Laboratory test showed an increase in Lactate Dehydrogenase (LDH), Gamma-Glutamyl Transpeptidase (GGT), Alpha Feto Protein (AFP), quantitative Hepatitis B Virus (HBV) DNA, and HBsAg reactive. Abdominal Multi-Slice Computed Tomography (MSCT) revealed malignant solid mass with necrotic component inside, indistinct borders, irregular margins and kissing spleen. Result: The diagnosis of liver cancer in this patient suggested HCC associated with chronic hepatitis B infection. Conclusion: Routine follow-up of all children with chronic hepatitis B infection is crucial because of the risk of developing liver cancer in adolescence and adulthood.